MANAGEMENT AND INTEGRATION OF BOARDING SCHOOL EDUCATIONAL ACTIVITIES IN DEVELOPING STUDENTS' MULTIPLE INTELLIGENCES - Mochamad Nurcholiq; Lisna Yunita; Vina Aula Rusdah (STAI Ma'had Aly Al-Hikam Malang, 2024)
Comprehensive education plays a crucial role in preparing students to contribute effectively to society. One approach to comprehensive education involves fostering multiple intelligences. The implementation of multiple intelligences programs is commonly found in boarding schools (pesantren). However, the management practices of these institutions vary across different establishments. This study was conducted at SMPI and Pondok Pesantren Miftahul Ulum using a case study methodology. Data was collected through interviews, observations, and document analysis. The data analysis was performed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings suggest that, first, the planning of boarding school education aimed at developing multiple intelligences in students is based on a well-defined vision and mission, as well as a flexible and inclusive curriculum structure. Second, the implementation of boarding school education is carried out through the development of various intelligences, including linguistic, logical-mathematical, spatial, kinesthetic, musical, interpersonal, intrapersonal, and naturalistic intelligences. Third, the evaluation of the educational process is conducted through several assessment steps: evaluation of academic and logical-mathematical intelligence, linguistic intelligence, interpersonal and intrapersonal intelligence, kinesthetic intelligence, musical intelligence, spatial intelligence, naturalistic intelligence, and holistic assessment. Keywords: Boarding School Management; Multiple Intelligences; Educational Integration; Student Development. Abstrak Pendidikan komprehensif memegang peranan penting dalam mempersiapkan peserta didik untuk berkontribusi secara efektif bagi masyarakat. Salah satu pendekatan pendidikan komprehensif adalah dengan mengembangkan kecerdasan majemuk. Penerapan program kecerdasan majemuk umumnya ditemukan di pesantren. Akan tetapi, praktik pengelolaan lembaga ini berbeda-beda di setiap lembaga. Penelitian ini dilakukan di SMPI dan Pondok Pesantren Miftahul Ulum dengan menggunakan metodologi studi kasus. Pengumpulan data dilakukan melalui wawancara, observasi, dan analisis dokumen. Analisis data dilakukan dengan menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa, pertama, perencanaan pendidikan pesantren yang bertujuan untuk mengembangkan kecerdasan majemuk pada peserta didik didasarkan pada visi dan misi yang jelas, serta struktur kurikulum yang fleksibel dan inklusif. Kedua, penerapan pendidikan pesantren dilakukan melalui pengembangan berbagai kecerdasan, meliputi kecerdasan linguistik, logika-matematika, spasial, kinestetik, musikal, interpersonal, intrapersonal, dan naturalistik. Ketiga, evaluasi proses pendidikan dilakukan melalui beberapa langkah penilaian: penilaian kecerdasan akademik dan logika-matematika, kecerdasan linguistik, kecerdasan interpersonal dan intrapersonal, kecerdasan kinestetik, kecerdasan musikal, kecerdasan spasial, kecerdasan naturalistik, dan penilaian holistik. Kata Kunci: Manajemen Pondok Pesantren; Kecerdasan majemuk; Integrasi Pendidikan; Pengembangan peserta didik.